2021
DOI: 10.1007/s12221-021-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Single-step Synthesis and Characterization of Zr-MOF onto Wool Fabric: Preparation of Antibacterial Wound Dressing with High Absorption Capacity

Abstract: Improvement of curative herbal extracts effectiveness through novel drug delivery systems is a field of study for the researches nowadays. Zirconium-based metal-organic frameworks (Zr-MOFs) are one of the most capable porous nanocarriers that need a biocompatible template to be used in biomedical applications. In this work, Zr-MOF was synthesized into the wool fabric through in-situ one-pot method with different molar ratios. The final fabrics were characterized thoroughly using various techniques and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…DFT coupled with the [LANL2DZ/6-31G+(d,p)] mixed basis set was employed to optimize geometrically the molecular structure of all isolated compounds within atom numbering as represented in Figure . The results displayed in Table 8Sa,b showed that (i) the bond lengths of the most characteristic functional groups for isolated complexes correlate with the IR band expansions, confirming their participation in the coordination process, and (ii) the bond angles of the [Cu­( o -BMP)­(H 2 O) 2 ]·2H 2 O and [Cd­( o -BMP)­(H 2 O) 2 ]·2H 2 O complexes correlate a distorted octahedral arrangement, while the [VO­( o -H 2 BMP)­(SO 4 )]·4H 2 O exists as a square-pyramidal geometry supporting the configurations concluded by UV–visible spectral analyses …”
Section: Resultsmentioning
confidence: 99%
“…DFT coupled with the [LANL2DZ/6-31G+(d,p)] mixed basis set was employed to optimize geometrically the molecular structure of all isolated compounds within atom numbering as represented in Figure . The results displayed in Table 8Sa,b showed that (i) the bond lengths of the most characteristic functional groups for isolated complexes correlate with the IR band expansions, confirming their participation in the coordination process, and (ii) the bond angles of the [Cu­( o -BMP)­(H 2 O) 2 ]·2H 2 O and [Cd­( o -BMP)­(H 2 O) 2 ]·2H 2 O complexes correlate a distorted octahedral arrangement, while the [VO­( o -H 2 BMP)­(SO 4 )]·4H 2 O exists as a square-pyramidal geometry supporting the configurations concluded by UV–visible spectral analyses …”
Section: Resultsmentioning
confidence: 99%
“…As a result, entanglement should be more difficult for the adjacent woolen fibers or yarns; this may be one of the reasons for the better permeability, and therefore the fabrics with regenerated wool had higher air permeability than the woolen fabrics. With the use of blends with other fibers [ 25 , 26 , 28 , 29 ] and surface treatment [ 30 , 31 , 33 , 34 ], the air permeability can be controlled. It was established that combined twill had the highest air permeability and derived basket weave the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…This property is highly related to the porosity of the fabric, of which the methods of establishment are described in reference [ 23 ]. The structural parameters, such as the raw material, linear density of the warp and weft yarns, number of yarn twists, warp and weft density, warp and weft crimp, and weave, influence the porosity and air permeability of fabrics [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The influence of the structure of woolen fabric on its comfort properties and shrinkage has been described in only a few works [ 25 , 26 ]; thus, such investigations are very important.…”
Section: Introductionmentioning
confidence: 99%
“…[4] One of the methods for preparing antibacterial fabrics is the synthesis of metal-based nanoparticles on them. [5][6][7] Among the metal oxides, copper-based nanoparticles have high antibacterial activities. [8][9][10][11][12] Facile preparation process and high surface area introduced by their nano-size, make them favorable antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%